Comparative critical genre analysis of statements on corporate governance of Malaysian corporations between pre and during currency depreciation - Hussain, Shabnum Sayyed (2021)
The statement on corporate governance (henceforth, SCG) is a sub-genre of corporate annual reports that is typically designed to inform about the structure and corporate governance standard operating procedures of corporations. Relevant research found that corporate writers during adverse financial circumstances, not only report corporate information but also establish a positive and trustworthy image of the corporations by using various rhetorical strategies. Malaysia has recently experienced adverse currency depreciation during 2014 to 2016. Therefore, this research aimed to investigate the rhetorical structure, linguistic features, and socio-cognitive strategies of the SCG genre. It also aimed to explore the effects of currency depreciation on the linguistic features that can project a positive and trustworthy image of the corporations. The research data comprised 240 SCG of 40 Malaysian corporations distributed between the Pre (2011- 2013) and During crisis (2014-2016) periods. The Critical Genre Theory is applied as a theoretical framework to get a better understanding of why the reports are written the way they are by knowing about the nature, form, and function of the SCG and the use and exploitation of this genre to communicate private intentions. The rhetorical structure analysis revealed 30 distinct moves and various steps. There are 9 obligatory moves, 9 conventional moves and 12 optional moves. The comparison of Pre and During crisis periods revealed an increase of 16 moves in the During crisis period. These moves report the assessment and independence of the board of directors, the financial and audit reporting, and the measures that corporations apply for the internal control and risk management. In addition, the current research found frequent use of personification, nominalization, passive voice, attitudinal adjectives and adverbs that made this genre evaluative as well as more explicitly objective. The comparison of the periods further indicated that Malaysian corporations significantly increased the use of these lexico-grammatical features in the During-crisis period. The findings also revealed that there is an overlap of two socio-cognitive strategies and three distinctive discourses integrated into the SCG genre. These socio cognitive strategies of genre mixing bended the norms of conventional reporting into a promotional one to establish a positive and trustworthy image of the Malaysian corporations. The description of the rhetorical structure provided a framework having 30 moves and various steps which are more significant for the disadvantaged readers and writers of English. The novice corporate writers and non-native learners of business writing can sharpen their reading and writing skills by getting awareness of the types of moves usually used in the SCG genre. The findings of linguistic features would also create awareness in English language teachers to identify the potential problems that corporate writers encounter at classrooms and workplaces typical to the SCG genre.